Are Shocks to Natural Gas Consumption Temporary or Permanent? Evidence From a Panel of U.S. States - Apergis, Nicholas; Loomis, D.; Payne, J. (Elsevier Science Ltd., 2010)
This short communication examines whether or not U.S. natural gas consumption follows a stationary process. Unlike previous research that has focused on regional country or industrial sector-based panel studies, this study undertakes a sub-national investigation of natural gas consumption for the 50 U.S. states. Levin et al. (2002), Im et al. (2003), Maddala and Wu (1999), and Hadri (2000) panel unit root and stationarity tests reveal that natural gas consumption is integrated of order one. However, once allowance is made for endogenously determined structural breaks, the Carrion-i-Silvestre et al. (2005), Im et al. (2005), and Westerlund (2005) panel unit root and stationarity tests indicate that natural gas consumption is integrated of order zero. Discussion of the structural breaks is briefly surveyed in relation to the natural gas industry’s response to legislative actions.